Uniformly-oriented pseudo-single crystal perovskite thin film and preparation method and application thereof

By introducing volatile solvent additives to coordinate with lead iodide in the preparation of perovskite films, the reaction kinetics are delayed, and the problem of random crystal quality and orientation of thin films in the two-step process is solved, and efficient preparation of uniformly oriented quasi-single crystal perovskite films is achieved, which significantly improves the performance and stability of solar cells.

CN119855460AActive Publication Date: 2025-04-18NANKAI UNIV
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202510322689.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-19
Publication Date
2025-04-18
Estimated Expiration
2045-03-19

AI Technical Summary

Technical Problem

In the existing two-step perovskite film preparation process, the precursor reaction is uncontrollable, resulting in poor crystallization quality and random orientation of the film, affecting the photoelectric conversion efficiency and long-term stability of solar cells.

Method used

By introducing volatile solvent additives with different coordination abilities to coordinate with lead iodide, the subsequent kinetic process of reaction between organic amine salt and lead iodide is delayed, the crystallinity and orientation of perovskite films are regulated, and the efficient preparation of pure phase quasi-single crystal structures is achieved.

Benefits of technology

It effectively improves the crystal quality and orientation consistency of perovskite films, promotes interfacial carrier transmission and extraction, and significantly improves the photoelectric conversion efficiency and stability of perovskite solar cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119855460A_ABST
    Figure CN119855460A_ABST
Patent Text Reader

Abstract

The invention relates to the field of perovskite solar cells, and discloses a uniformly-oriented pseudo-single crystal perovskite thin film and a preparation method and application thereof.The preparation method comprises the steps that at least one of N, N-dimethyl propenylurea, methyl phenyl sulfoxide and ethanesulfinyl ethane serves as a solvent additive, the solvent additive and N, N-dimethyl formamide are prepared into an organic mixed solvent, and the organic mixed solvent is mixed with N, N-dimethyl formamide; dissolving lead iodide and cesium iodide and / or rubidium chloride in an organic mixed solvent, coating, and heating to obtain a lead iodide film; and depositing an organic amine salt solution on the lead iodide thin film, and performing annealing treatment to obtain the perovskite thin film. By introducing the solvent additives with different coordination capabilities, the reaction activity of the lead iodide precursor is reduced, and the kinetic process of the perovskite generation reaction is effectively delayed, so that the sufficient reaction of the organic amine salt and the lead iodide intermediate phase is promoted; the problems of residual lead iodide impure phase in the perovskite thin film and poor crystallization quality in a traditional two-step method are effectively solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of perovskite solar cells, and in particular to a uniformly oriented quasi-single crystal perovskite film and a preparation method and application thereof. Background Art

[0002] Organic-inorganic hybrid perovskite materials have become the representative materials of the third generation of new solar cells due to their wide chemical tunability and excellent semiconductor properties. The certified photoelectric conversion efficiency of single-junction devices of perovskite solar cells constructed based on this material has been greatly improved from the initial 3.8% to 26.7%. The preparation process of perovskite film is a key factor in determining the crystallization quality and phase composition of the film, which directly affects the photoelectric conversion efficiency of solar cells and the long-term operation stability of the device. The preparation methods of perovskite films are mainly divided into two categories: one-step method and two-step method. The one-step method completes the film preparation by directly depositing the perovskite precursor solution on the substrate; while the two-step method first prepares a uniform lead iodide (PbI2) film on the substrate, and then reacts with lead iodide by spin coating or immersion in an organic amine salt solution (AX, such as formamidine iodide, FAI) to form a perovskite film. The two-step method has good process controllability and film uniformity, and is compatible with vacuum processes, so it has important application potential in the industrialization of perovskite solar cells.

[0003] Although the two-step method has significant advantages, there is still the problem of uncontrollable precursor reaction, which leads to poor film crystallization quality and random orientation, which ultimately affects the photoelectric conversion efficiency and long-term stability of the device. The existing strategy usually introduces additive molecules into the lead iodide precursor solution to generate a low-dimensional perovskite phase on the surface of the perovskite grains to achieve the purpose of passivating the grain boundary and prevent the perovskite from decomposing under operating conditions. However, this method still has the problem of introducing additives to affect the crystallization quality of perovskite, and such additives will induce the formation of low-dimensional perovskites, resulting in the obstruction of carrier transport inside the perovskite, further limiting the carrier transport efficiency and device performance improvement. Therefore, the preparation process of the traditional two-step perovskite film needs to be further improved. The present invention regulates the two-step reaction by introducing a volatile solvent as an additive. Such additives can be completely volatilized during the perovskite annealing process, and the crystallization performance of the perovskite film is non-destructively regulated without introducing a miscellaneous phase, so as to achieve the controllable construction of a uniformly oriented quasi-single-crystalline perovskite film, and based on this active layer preparation technology, a high-efficiency and high-stability perovskite solar cell preparation is achieved. Summary of the invention

[0004] In the traditional process of preparing perovskite films by two-step method, the excess lead iodide is often converted into a low-dimensional perovskite phase by introducing organic amine salts or amino acid additives. However, the carrier mobility of low-dimensional perovskite materials is usually significantly lower than that of bulk perovskites, resulting in limited carrier transport inside the film and hindering the efficient extraction of carriers at the interface of the device. In addition, there is a strong coordination effect between such additives and lead iodide, which is easy to compete with the perovskite formation reaction, thereby significantly reducing the crystallization quality of the film and limiting the further improvement of device performance. In order to solve the problem of film crystallization quality caused by the uncontrollable reaction of lead iodide and formamidine iodide, the present invention proposes a strategy of delaying the subsequent AX+PbI2 reaction kinetic process by introducing a volatile solvent additive with different coordination abilities to coordinate with lead iodide. This method aims to improve the crystallinity of perovskite polycrystalline films, regulate the orientation of polycrystalline films, and realize the efficient preparation of pure phase quasi-single crystal structure perovskite films to promote interface carrier extraction, thereby significantly improving the performance and stability of perovskite solar cells.

[0005] To achieve the above object, on the one hand, the present invention provides a method for preparing a uniformly oriented quasi-single-crystalline perovskite film, which comprises the following steps:

[0006] S1. Using at least one of N,N-dimethylpropylene urea, methylphenyl sulfoxide, and ethylsulfinylethane as a solvent additive, the solvent additive is mixed with N,N-dimethylformamide to prepare an organic mixed solvent, and lead iodide and cesium iodide and / or rubidium chloride are dissolved in the organic mixed solvent to obtain a lead iodide solution, wherein the molar ratio of the solvent additive to lead iodide is preferably 0.3-1.3:1; adopting a coating film-forming method, first coating the lead iodide solution, and then heating it at 50-75°C to obtain a lead iodide film; the coating process is any one of spin coating, scraper coating, and spray coating.

[0007] S2. Dissolve at least one of formamidine iodide, methylammonium chloride, and methylammonium iodide in an isopropanol solvent to obtain an organic amine salt solution; deposit the organic amine salt solution on the lead iodide film to obtain a brown perovskite film, and then anneal at 135-150°C to remove solvent additives and improve the perovskite crystal quality, thereby obtaining a uniformly oriented quasi-single crystal perovskite film.

[0008] As a further preferred technical solution of the present invention, in step S1, the heating treatment time is 0.5-2 min.

[0009] As a further preferred technical solution of the present invention, in step S2, the annealing treatment time is 5-20 min.

[0010] As a further preferred technical solution of the present invention, in step S1, the molar ratio of the solvent additive to lead iodide is 0.3-1.3:1, and more preferably 0.5:1.

[0011] As a further preferred technical solution of the present invention, the dosage ratio of each component in the lead iodide solution is: 1 mL of organic mixed solvent, 1.5 mmol of lead iodide, 0.05 mmol of cesium iodide or 0.05 mmol of rubidium chloride.

[0012] According to another aspect of the present invention, the present invention also provides a uniformly oriented quasi-single-crystalline perovskite film, which is prepared by the above method.

[0013] According to another aspect of the present invention, the present invention also provides an application of a uniformly oriented quasi-single-crystalline perovskite film in a perovskite solar cell, wherein the perovskite solar cell comprises a transparent conductive substrate, and a tin dioxide electron transport layer, a perovskite active layer, a quasi-two-dimensional perovskite passivation layer, a hole transport layer and a metal electrode sequentially arranged on the transparent conductive substrate, or a hole transport layer, a quasi-two-dimensional perovskite passivation layer, a perovskite active layer, a tin dioxide electron transport layer and a metal electrode sequentially arranged on the transparent conductive substrate; wherein the perovskite active layer is a uniformly oriented quasi-single-crystalline perovskite film prepared according to the above-mentioned preparation method, and the transparent conductive substrate is a glass substrate coated with fluorine-doped tin oxide (FTO) or indium-doped tin oxide (ITO).

[0014] As a further preferred technical solution of the present invention, the quasi-two-dimensional perovskite passivation layer is obtained by coating an isopropanol solution of an aromatic and alkylamine salt to form a film, wherein the chemical structural formula of the aromatic and alkylamine salt is AX, A is one of phenylethylamine, amphetamine, phenbutylamine, n-hexylamine, and n-octylamine cations, and X is I - Br - , Cl - One of them.

[0015] Compared with the prior art, the present invention can achieve the following beneficial effects:

[0016] In the two-step perovskite film preparation process of the present invention, by introducing solvent additives with different coordination abilities, the reactivity of the lead iodide precursor is reduced, the kinetic process of the perovskite formation reaction is effectively delayed, and the full reaction of the organic amine salt and the lead iodide intermediate phase is promoted. This method effectively delays the reaction rate of the two-step method, and realizes the orientation regulation of the perovskite polycrystalline film, successfully prepares a quasi-single-crystalline perovskite film with uniform orientation (hereinafter referred to as the perovskite film), and significantly promotes the interface carrier transport and extraction. The single-junction small-area perovskite solar cell prepared based on this method has a certified photoelectric conversion efficiency of more than 26.8%. In addition, the operating stability of the packaged device at 85°C and 50% relative humidity is significantly improved.

[0017] The two-step perovskite film preparation process of the present invention effectively solves the problem of residual lead iodide impurities and poor crystal quality in the perovskite film in the traditional two-step method. By introducing solvent additives, not only can the crystal quality of the final film be improved, but also the solvent additives can be ensured to be completely volatilized during the annealing process to avoid the introduction of other impurities. This provides an innovative solution for the controllable preparation of pure phase quasi-single crystal perovskite films with uniform orientation. The perovskite film prepared based on this method has been successfully applied to high-performance and high-stability perovskite solar cells, significantly improving the fill factor of the device, and showing excellent operating stability under harsh conditions (such as high temperature and high humidity environments). BRIEF DESCRIPTION OF THE DRAWINGS

[0018] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments.

[0019] Figure 1 3 are the morphology diagrams of the perovskite films of the control example and examples 1 to 3.

[0020] Figure 2 The perovskite films of the comparative example and examples 1 to 3 were subjected to slightly incident wide-angle X-ray scattering.

[0021] Figure 3 The reverse sweep current-voltage curves and device parameters of the battery device of the comparative example and examples 1 to 3 are shown.

[0022] Figure 4 The steady-state efficiency output of the battery devices of the control example and examples 1 to 3 at 85° C. and 50% relative humidity.

[0023] Figure 5 The efficiency statistics are for the control example and a series of devices prepared by changing the ratio of solvent additives based on Example 3.

[0024] The purpose, features and advantages of the present invention will be further described with reference to the accompanying drawings in conjunction with the embodiments. DETAILED DESCRIPTION

[0025] The specific implementation of the present invention is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described here is only used to illustrate and explain the present invention, and is not used to limit the present invention.

[0026] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The test reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the experimental methods, unless otherwise specified, are all conventional methods.

[0027] Embodiment 1:

[0028] The method for preparing the perovskite solar cell provided in this embodiment is as follows:

[0029] Step 1: Cleaning of transparent conductive substrate:

[0030] The glass substrate coated with fluorine-doped tin oxide (FTO) was ultrasonically cleaned with glass cleaning agent, deionized water and ethanol for 15 min respectively; then plasma cleaning was performed for 10 min and set aside.

[0031] Step 2: Preparation of tin dioxide electron transport layer:

[0032] The tin dioxide nanoparticle colloidal solution is deposited on a transparent conductive substrate by a spin coating method, or the tin dioxide electron transport layer is prepared by a chemical bath deposition method.

[0033] Step 3: Preparation of active layer (perovskite film) based on two-step method:

[0034] First, solution preparation:

[0035] 1.5 mmol lead iodide (PbI2) and 0.05 mmol cesium iodide (CsI) were uniformly dissolved in an organic mixed solvent of 90 μL N,N-dimethylpropylene urea and 910 μL N,N-dimethylformamide, and heated and stirred until fully dissolved to obtain a lead iodide solution;

[0036] Dissolve 0.5 mmol of formamidine iodide (FAI) and 0.2 mmol of methylammonium chloride (MACl) in 1 mL of isopropanol and stir until fully dissolved to obtain an organic amine salt solution.

[0037] Then, the perovskite film was prepared in two steps:

[0038] (1) The substrate obtained in step 2 was transferred to the inside of the glove box, 20 μL of lead iodide solution was transferred to the substrate, and the substrate was coated by spin coating at an acceleration of 2000 rpm / s and a rotation speed of 2000 rpm for 30 s; after the spin coating process was stopped, the wet film was transferred to a 70 °C hot stage for annealing for 40 s to obtain a lead iodide film;

[0039] (2) The lead iodide film was cooled to room temperature, and 100 μL of the organic amine salt solution was transferred onto the lead iodide film. The film was then spin-coated at an acceleration of 2000 rpm / s and a rotation speed of 2000 rpm for 30 s. After the spin coating process was stopped, the film was quickly transferred to an air environment with a relative humidity of ~35% and annealed on a hot plate at 150 °C for 10 min.

[0040] Step 4: Preparation of quasi-two-dimensional perovskite passivation layer:

[0041] Pipette 100 μL of 10 mM phenbutylamine hydrobromide isopropanol solution onto the active layer prepared in step 3 and spin coat at 4000 rpm / s for 30 s.

[0042] Step 5: Preparation of hole transport layer:

[0043] (1) Dissolve 72.3 mg of 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (Spiro-OMeTAD) in 1 mL of chlorobenzene; add 30 μL of tetra-tert-butylpyridine (tBP) and 36 μL of 260 mg / mL lithium bis(trifluoromethylsulfonyl)imide (LiTFSI) acetonitrile solution to prepare a mixed solution;

[0044] (2) Pipette 30 μL of the mixed solution and homogenize at 4000 rpm / s for 30 s.

[0045] Step 6: Metal electrode deposition:

[0046] Using vacuum evaporation method, 5×10 -4 Under a vacuum degree of Pa, a gold electrode with a thickness of 80 nm was evaporated at a rate of 2 Å / s, and the preparation of the perovskite solar cell device was finally completed.

[0047] Embodiment 2:

[0048] The only difference from Example 1 is that the solvent additive used to prepare the lead iodide solution is different, that is, 90 μL of N,N-dimethylpropylene urea in Example 1 is replaced by 100 μL of methyl phenyl sulfoxide, and mixed with 900 μL of N,N-dimethylformamide to obtain 1 mL of organic mixed solvent.

[0049] Embodiment three:

[0050] The only difference from Example 1 is that the solvent additive used to prepare the lead iodide solution is different, that is, 90 μL of N,N-dimethylpropylene urea in Example 1 is replaced by 80 μL of ethylsulfinylethane, and mixed with 920 μL of N,N-dimethylformamide to obtain 1 mL of organic mixed solvent.

[0051] Comparative Example:

[0052] As a control experiment of the above three groups of embodiments, the only difference from Example 1 is that the solvent additive used to prepare the lead iodide solution is different, that is, 90 μL of N,N-dimethylpropylene in Example 1 is replaced with 60 μL of dimethyl sulfoxide, and mixed with 940 μL of N,N-dimethylformamide to obtain 1 mL of mixed solvent.

[0053] The perovskite films prepared in Examples 1 to 3 and the comparative example were characterized as follows:

[0054] Scanning electron microscopy (SEM) film morphology Figure 1 As shown. It can be seen that the perovskite grain size of the control example is small and the crystal quality is poor; the lead iodide particles of Example 1 are significantly reduced compared with the control example, and the grain size of Example 2 is further improved compared with Example 1; the average grain size of Example 3 is about 1.5 μm and uniform, and its effect is the best.

[0055] The film is slightly incident on wide angle X-ray scattering. Figure 2 As shown. It can be seen that the film of the control example clearly has a lead iodide diffraction peak (q = 0.9 Å -1 ), and the perovskite polycrystalline film has no obvious orientation; the lead iodide diffraction peak intensity in Example 1 decreases, and the (100) diffraction peak (q = 1.0 Å -1 ) intensity is improved, proving that the crystallinity of the film is improved; in Example 2, the lead iodide diffraction peak disappears completely, and the perovskite (100) diffraction peak shows a dominant orientation; in Example 3, the lead iodide diffraction peak disappears completely, and the film has a uniform orientation.

[0056] The photoelectric conversion efficiency and stability of the perovskite solar cell devices prepared in Examples 1 to 3 and the control example were tested as follows:

[0057] Under AM1.5G sunlight, the test mask area is 0.064 cm 2 , test device forward and reverse sweep current-voltage characteristic curve ( Figure 3 ), and test the device operation stability in an environmental chamber with 50% relative humidity and 85°C ( Figure 4 ). Comparison shows that compared with the control example, the device fill factor of Example 1 is significantly improved, and the device stability is also improved; the device fill factor of Example 2 is further improved, and the device efficiency attenuation is reduced to 5% after 1000 hours of aging test at 85°C and 50% humidity; the device efficiency of Example 3, which won the championship, is 27.05%, and the device efficiency has no obvious attenuation after 1000 hours of aging test at 85°C and 50% humidity.

[0058] In order to further demonstrate the beneficial technical effects of the present invention, based on the technical scheme of Example 3, the amount ratio of the solvent additive (ethylsulfinylethane) used to prepare the lead iodide solution relative to the lead iodide is changed, and the photoelectric conversion efficiency of the finally prepared series of perovskite solar cell devices is tested. The specific parameters and test results are shown in Table 1 and Figure 5 shown.

[0059] Table 1

[0060]

[0061] From the data analysis in Table 1, it can be seen that the amount of the solvent additive (ethanesulfenylethane) is less than 1.3 times that of lead iodide, which has an excellent improvement effect on the photoelectric performance of the battery device and can effectively solve the problem of residual lead iodide impurities and poor crystal quality in the perovskite film in the traditional two-step method, thus affecting the battery performance. After a large number of experiments, the molar ratio of the solvent additive to lead iodide is preferably 0.3-1.3:1, and the best effect is achieved when the molar ratio is 0.5:1.

[0062] Although specific embodiments of the present invention are described above, those skilled in the art should understand that these are merely examples and that various changes or modifications may be made to the embodiments without departing from the principles and essence of the present invention. The scope of protection of the present invention is limited only by the appended claims.

Claims

1. A method for preparing a uniformly oriented quasi-single-crystalline perovskite film, characterized in that: The following steps are involved: S1, using at least one of N,N-dimethylpropylene urea, methylphenyl sulfoxide, and ethylsulfinylethane as a solvent additive, mixing the solvent additive with N,N-dimethylformamide to prepare an organic mixed solvent, dissolving lead iodide and cesium iodide and / or rubidium chloride in the organic mixed solvent to obtain a lead iodide solution, wherein the molar ratio of the solvent additive to the lead iodide is 0.3-1.3:1; A coating film-forming method is adopted, wherein the lead iodide solution is coated, and then the lead iodide film is obtained by heating. S2, dissolving at least one of formamidine iodide, methylammonium chloride, and methylammonium iodide in an isopropanol solvent to obtain an organic amine salt solution; The organic amine salt solution is deposited on the lead iodide film, and then annealed at 135-150° C. to obtain a uniformly oriented quasi-single-crystalline perovskite film.

2. The method for preparing a uniformly oriented quasi-single-crystalline perovskite thin film according to claim 1, characterized in that: In step S1, the heating treatment temperature is 50-75°C.

3. The method for preparing a uniformly oriented quasi-single-crystalline perovskite thin film according to claim 2, characterized in that: In step S1, the heating treatment time is 0.5-2 min.

4. The method for preparing a uniformly oriented quasi-single-crystalline perovskite thin film according to claim 1, characterized in that: In step S2, the annealing treatment time is 5-20 min.

5. The method for preparing a uniformly oriented quasi-single-crystalline perovskite thin film according to claim 1, characterized in that: In step S1, the molar ratio of the solvent additive to lead iodide is 0.3-1.3:

1.

6. The method for preparing a uniformly oriented quasi-single-crystalline perovskite thin film according to claim 1, characterized in that: The dosage of each component in the lead iodide solution is: 1 mL of organic mixed solvent, 1.5 mmol of lead iodide, 0.05 mmol of cesium iodide or 0.05 mmol of rubidium chloride.

7. A uniformly oriented quasi-single-crystalline perovskite film, characterized in that: The method is prepared by any one of claims 1 to 6.

8. Use of the uniformly oriented quasi-single-crystalline perovskite film according to claim 7 in perovskite solar cells.

9. The use according to claim 8, characterized in that: The perovskite solar cell includes a transparent conductive substrate, and a tin dioxide electron transport layer, a perovskite active layer, a quasi-two-dimensional perovskite passivation layer, a hole transport layer and a metal electrode arranged in sequence on the transparent conductive substrate, or a hole transport layer, a quasi-two-dimensional perovskite passivation layer, a perovskite active layer, a tin dioxide electron transport layer and a metal electrode arranged in sequence on the transparent conductive substrate, wherein the perovskite active layer is a uniformly oriented quasi-single crystal perovskite film.

10. The use according to claim 9, characterized in that: The quasi-two-dimensional perovskite passivation layer is obtained by coating an isopropanol solution of an aromatic and alkylamine salt to form a film, wherein the chemical structural formula of the aromatic and alkylamine salt is AX, wherein A is one of phenylethylamine, amphetamine, phenbutylamine, n-hexylamine, and n-octylamine cations, and X is I - Br - , Cl - One of them.

Citation Information

Patent Citations

  • Defect and stress regulating agent for FA1-xCsxPbBryI3-y perovskite thin film, regulating method and application

    CN116406212A

  • Method for preparing formamidine lead iodide perovskite thin film at low temperature, thin film, method for preparing photovoltaic device and photovoltaic device

    CN116669508A

  • Cesium-formamidine-based lead-iodine alloy perovskite active layer and preparation method and application thereof

    CN117794334A

  • A method for preparing perovskite film

    CN118119243A

  • Perovskite precursor solution, perovskite thin film, preparation method of perovskite thin film and solar cell

    CN118139497A